PENGEMBANGAN MEDIA BIG BOOK DUA DIMENSI MATERI PERPINDAHAN KALOR/PANAS PADA MATA PELAJARAN IPA KELAS V SEKOLAH DASAR - Rafika Duri; Hetilaniar; Aldora Pratama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research was motivated by the emergence of problems at SD Negeri 57 Palembang, namely the absence of interesting and varied learning media in the use of learning media in the learning process, so that students were less interested in participating in learning which caused students to find it difficult to understand the material presented by educators. The purpose of the research is to develop two-dimensional digital big book learning media in order to determine the validity and practicality of the developed big book media. The type of research used is Research and Development (R&D) with the ADDIE model which consists of 5 stages, namely the Analysis stage, the Design Stage, the Development Stage, the Implementation Stage and the Evaluation Stage. The results of the big book learning media research were declared valid, shown in the average percentage results with validation results by material expert validation, namely 87.14% in the "Very Valid" category. The average percentage obtained by media expert validation is 71% with the "Valid" category. As for the average percentage obtained by linguist validation, which is equal to 80% with the "Valid" category from the results of this percentage, the big book media has quality, appearance and content design that is in accordance with the development of students. The results obtained in validation one to one obtained a percentage of 90.4% with the criteria "Very Practical", while in the small group trial it was 82.1% with the criteria "Very Practical". The media developed is in accordance with the level of development of students, communicative. It is concluded that the big book learning media on heat transfer material at SD Negeri 57 Palembang which was developed is very feasible, valid and very practical to use as a learning medium.